2011
DOI: 10.1093/hmg/ddr063
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral small-vessel disease protein HTRA1 controls the amount of TGF-β1 via cleavage of proTGF-β1

Abstract: Cerebral small-vessel disease is a common disorder in elderly populations; however, its molecular basis is not well understood. We recently demonstrated that mutations in the high-temperature requirement A (HTRA) serine peptidase 1 (HTRA1) gene cause a hereditary cerebral small-vessel disease, cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL). HTRA1 belongs to the HTRA protein family, whose members have dual activities as chaperones and serine proteases and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
94
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 35 publications
0
94
1
Order By: Relevance
“…Among 15 NMD-related factors, we identified that SMG-8 can suppress NMD efficiently with minimum cytotoxic effects. The ability of SMG-8 knockdown to efficiently suppress NMD was confirmed using another PTC-containing cell line from a patient with cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL) (12,30).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Among 15 NMD-related factors, we identified that SMG-8 can suppress NMD efficiently with minimum cytotoxic effects. The ability of SMG-8 knockdown to efficiently suppress NMD was confirmed using another PTC-containing cell line from a patient with cerebral autosomal recessive arteriopathy with subcortical infarcts and leukoencephalopathy (CARASIL) (12,30).…”
mentioning
confidence: 84%
“…However, if NMD degrades aberrant proteins that retain some normal cell function, disease conditions are exacerbated. There are many examples of mutant proteins that are degraded by NMD that retain some residual activity and partially normal function, resulting in an exacerbation of the defects caused by the original mutation (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…This led the authors to propose the lack of TGF-processing as a critical disease mechanism. 101 Contrasting these findings, a more recent study in HTRA1-deficient mice and CARASIL patient cells revealed a facilitating role of HtrA1 on the TGF-pathway. 35 The same study showed that LTBP-1 is a substrate for HtrA1.…”
Section: Cerebral Autosomal Recessive Arteriopathy With Subcortical Imentioning
confidence: 96%
“…This mechanism regulates the amount of mature TGF-"1. 24 No disease-specific therapy for CARASIL is available at this time.…”
Section: Cerebral Autosomal Dominantmentioning
confidence: 99%